Profile of T cells after dexamethasone treatment in BABL/c mice - Iga Dwi Januarisasi; Muhaimin Rifa'i (University of Brawijaya, 2015)
ABSTRACT Regulation of homeostatic mechanisms and the development of T lymphocytes is influenced by several things, one of them is glucocorticoids. Dexamethasone is a synthetic glucocorticoid drugs used in the treatment for several diseases acted as an anti-inflammatory. The aim of this experiment was to confirm the effect of dexamethasone at normal dose and high dose on T cell profile and also to know the quantity of T cells after dexamethasone injection in each dose. This experiment we applied 18 mice in the age of 2 week and divided into 3 treatment groups with six replication i.e. control, dexamethasone injection with normal dose (0.5 mg/kg BW) and high dose (10 mg/kg BW), then observed on day-7 after injection. T cells were isolated from the spleen and analyzed by flow cytometry. Data analysis was confirmed with the ANOVA test followed by Turkey test with significance different (α) of 0.05. The result showed that dexamethasone act as immunosuppressant agent on high dose (10 mg/kgBB). Dexamethasone injection with normal dose on healthy mice showed no significant different in total number of CD4+, CD8+, CD4+CD62L, and CD8+CD62L compared to control. But, dexamethasone injections with high dose showed that the total number of CD4+, CD8+, CD4+CD62L, and CD8+CD62L were decreased significantly. Key words: Dexamethasone, Flowcyto metry, Glucocorticoid, Immunosuppressant, T lymphocyte.